Case Report: Rectal Perforation Secondary to a Toothbrush in an Elderly Man - Aimanan, Karthigesu; Lim, Soon Yee; Ahmad Hamidi, Ahmad Junaidi; Chieng, Tiong How; Hayati, Firdaus (Frontiers in Surgery, 2022)
Rectal foreign bodies often constitute an arduous diagnosis and perplexing management. A 72-year-old gentleman who is mentally sound was brought to the emergency department for severe epigastric pain of a 1-week duration. On examination, he was pyrexial and in sepsis. The abdomen was guarded. A digital rectal examination was normal. Erect chest radiography revealed air under the diaphragm and abdominal radiography showed neither dilated bowel nor foreign body. A diagnostic laparoscopy was performed which revealed a yellow hard rod-shaped foreign body at the pelvis. Upon conversion to midline laparotomy, the foreign body was found to be a toothbrush with intraperitoneal rectal perforation of 1 cm in length. The brush was removed and the perforation was repaired primarily. A diverting transverse loop colostomy was created. Rectal foreign bodies may cause life-threatening rectal injuries including lacerations, bleeding, perforation, and obstruction. It is deemed crucial that any patient with rectal foreign body demands an orderly approach with the intention of diagnosis, management, and post-extraction evaluation.